2021
DOI: 10.1186/s12864-021-07896-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of miRNAs in skeletal muscle development at New Zealand rabbits

Abstract: Background miRNA is one of the crucial roles in the complex and dynamic network that regulates the development of skeletal muscle. The landscape of skeletal muscle miRNAs from fetus to adult in New Zealand rabbits has not been revealed yet. Results In this study, nine RNA-seq libraries of fetus, child and adult rabbits’ leg muscles were constructed. A total of 278 differentially expressed miRNAs (DEmiRNAs) were identified. In the fetus vs. child gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To better understand the RNA regulatory networks during skeletal muscle development in rabbits, we retrieved differentially expressed miRNAs during skeletal muscle development in rabbits in one previous study [ 30 ] and identified putative DEC-DEmiRNA interactions using miRanda software. We obtained 1594 DEC–DEmiRNA interaction pairs from D0 to D35 ( Figure 6 A and Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the RNA regulatory networks during skeletal muscle development in rabbits, we retrieved differentially expressed miRNAs during skeletal muscle development in rabbits in one previous study [ 30 ] and identified putative DEC-DEmiRNA interactions using miRanda software. We obtained 1594 DEC–DEmiRNA interaction pairs from D0 to D35 ( Figure 6 A and Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The differentially expressed miRNAs during the skeletal muscle development of rabbits were retrieved from a previous study conducted by Jing and colleagues [ 30 ]. The sequences of mature miRNA were retrieved from miRbase [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The KEGG analysis identified several enriched pathways might be associated with the development process, e.g., AMPK signaling, MAPK signaling, RNA degradation, and tight junction pathways. The MAPK signaling pathway has also been associated with miRNA-target regulation in animal development ( Kaitetzidou et al, 2015 ; Wang et al, 2017 ; Jing et al, 2021 ). Moreover, several sex hormone-related pathways were enriched for DEMs’ target transcripts in the earliest pairwise comparison (DS2 vs DS1), including aldosterone synthesis and secretion, GnRH signaling, and ovarian steroidogenesis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have characterized miRNAs’ functional importance in diverse biological processes, such as growth ( Yi et al, 2014 ), tissue regeneration ( Rajaram et al, 2014 ), environmental stress ( Sun et al, 2020 ), and immune responses ( Qiao et al, 2021 ). To date, several studies have focused on the miRNAs’ roles of gene regulation during animal development ( Alberti and Cochella, 2017 ; Chen et al, 2020 ; Wu et al, 2020 ; Jing et al, 2021 ; Kusama et al, 2021 ). In teleosts, the dynamics of gene expression and its regulation in early development have been described in model fishes, such as zebrafish ( Danio rerio ) ( Nepal et al, 2016 ; Kasper et al, 2017 ; Shi et al, 2020 ) and medaka ( Oryzias latipes ) ( Tani et al, 2010 ), and important aquaculture species ( Rasal et al, 2016 ; Herkenhoff et al, 2018 ), such as rainbow trout ( Oncorhynchus mykiss ) ( Ramachandra et al, 2008 ), turbot ( Scophthalmus maximus ) ( Robledo et al, 2017 ), Nile tilapia ( Oreochromis niloticus ) ( Pinhal et al, 2018 ), European sea bass ( Dicentrarchus labrax ) ( Sarropoulou et al, 2019 ), and the common carp ( Cyprinus carpio ) ( Wang et al, 2017 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the process of skeletal muscle development, some muscle-specific miRNAs or muscle-rich expressions of miRNAs involved in myogenesis were reported. For example, miR-185-3p and miR-370-3p are highly and specifically expressed in leg muscles of New Zealand rabbit fetuses, children, and adults, affecting muscle development [ 11 ], and miR-22 can inhibit the proliferation of C2C12 cells and promote their differentiation [ 12 ]. More and more studies indicate that multiple muscle-enriched miRNAs play an extremely important and essential role in muscle development.…”
Section: Introductionmentioning
confidence: 99%